Spodbujanje in spremljanje bralnih navad učencev tretjega triletja osnovne šole - Janeš, Lidija (Šolska knjižnica, 2012)
Students' reading is closely linked to teaching performance, so librarians and educators strive to motivate the students to develop or promote a positive view to read, which includes the idea of what reading really is and what it is for. Librarians encourage the students to work through a variety of activities in order to realize that reading is the activity which allows them to grasp the meaning of the text and through which they can learn. The results of a survey conducted on a sample of pupils in the third triad in a Slovenian primary school clearly define teenage reading habits. They are quite alarming. For the purpose of improving the reading habits and motivation to read we presented examples from practice based on the participation of librarians in the educational planning process and co-operating with teachers.
Keywords: bralna motivacija; bralna uspešnost; bralna vzgoja; branje; osnovne šole; razlike med spoloma; šolske knjižnice; učenci